Autologous Tenocyte Injection for the Treatment of Severe, Chronic Resistant Lateral Epicondylitis: A Pilot Study. (December 2013) - Wang, Allan; Breidahl, William; Mackie, Katherine E.; Lin, Zhen; Qin, An; Chen, Jimin; Zheng, Ming H.
Background: Severe chronic lateral epicondylitis (LE) is associated with degenerative tendon changes, extracellular matrix breakdown, and tendon cell loss. On the basis of positive outcomes from preclinical studies, this study is the first clinical trial of autologous tenocyte injection (ATI) on severe tendinopathy associated with chronic LE. Hypothesis: Autologous tenocyte injection is a safe and effective procedure that enables a reduction in pain and improvement in function in resistant LE. Study Design: Case series; Level of evidence, 4. Methods: Patients with severe refractory LE underwent clinical evaluation and magnetic resonance imaging (MRI) before intervention. A patellar tendon needle biopsy was performed under local anesthetic, and tendon cells were expanded by in vitro culture. Tenocytes used for the injection were characterized by flow cytometry and real-time polymerase chain reaction. Autologous tenocytes were injected into the site of tendinopathy identified at the origin of the extensor carpi radialis brevis tendon under ultrasound guidance on a single occasion. Patients underwent serial clinical evaluations and repeat MRI at 12 months after intervention. Results: A total of 20 consecutive patients were included in the study. Three patients withdrew consent after enrollment and before ATI. No adverse event was reported at either biopsy or injection sites. Furthermore, no infection or excessive fibroblastic reaction was found in any patient at the injection site. Clinical evaluation revealed an improvement in mean visual analog scale scores, for a maximum pain score from 5.94 at the initial assessment to 0.76 at 12 months ( P < .001). Mean quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) and grip strength scores also significantly improved over the 12-month follow-up (QuickDASH score, 45.88 [baseline] to 3.84; grip strength, 20.17 kg [baseline] to 37.38 kg; P < .001). With use of a validated MRI scoring system, the grade of tendinopathy at the common extensor origin improved significantly by 12 months ( P < .001). One patient elected to proceed to surgery 3 months after ATI following a reinjury at work. Conclusion: In this study, patients with chronic LE who had previously undergone an unsuccessful full course of nonoperative treatment showed significantly improved clinical function and structural repair at the origin of the common extensor tendon after ATI. This novel treatment is encouraging for the treatment of tendinopathy and warrants further evaluation.